Enhanced biomass and lipid production from olive processing wastewater using Scenedesmus obliquus in a two-stage cultivation strategy under salt stress - Nicodemou, Andonia; Konstantinou, Despoina; Koutinas, Michalis (My University, 2024)
The study enhanced Scenedesmus obliquus cultivation via optimization of C/N and C/P ratios in synthetic media and evaluation of a two-stage cultivation strategy through application of salinity stress in olive processing wastewater-based feedstocks. S. obliquus under 40/1 C/N ratio performed biomass and lipid productivity that reached 0.15 and 34.1 mg L−1 d−1 respectively, demonstrating high glucose removal efficiency. Application of a two-stage cultivation strategy employing 0, 10, 20 and 30 g L−1 NaCl during the second bioprocess segment resulted in elevated biomass productivity (0.14–0.19 g L−1 d−1), which was reduced under batch mode yielding 0.11 g L−1 d−1. Two-stage cultivation triggered higher lipid productivity (4.2%-156.9%) following 3 d and 6 d upon the onset of the second stage (42.7–55.2 mg L−1 d−1) as compared to batch conditions, while the utilization of reducing sugars in exhausted olive pomace hydrolysates and table olive processing wastewater reached 53.6%-61.2%. Proline, glycerol and reactive oxygen species accumulated at considerable levels employing 20 and 30 g L−1 NaCl, indicating that S. obliquus expressed cellular stress under elevated salinity content, which was not notably stimulated using 10 g L−1 NaCl. The use of olive processing wastewater in a two-stage cultivation strategy under stress conditions enables future development of algal biorefinery systems for production of S. obliquus biomass and polyunsaturated fatty acids as high added-value products from biowaste.
Keywords: Lipids; Olive processing wastewater; Proline; Salt stress; Scenedesmus obliquus; Two-stage cultivation